2014
DOI: 10.14740/jnr291w
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Neurodegenerative Ataxias With Intravenous Immune Globulin

Abstract: Background: Neurodegenerative ataxias, including spinocerebellar ataxias (SCAs), are progressive diseases without effective treatment. There is preclinical evidence that inflammation may contribute to neuronal injury in several neurodegenerative ataxias. Intravenous immune globulin (IVIG) is a therapeutic modality that is used as treatment of several autoimmune and inflammatory disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In an open-label pilot study, patients with SCA3 receiving IVIG treatment demonstrated improvement in the clinical disability scores. Following the nal course of IVIG treatment, total SARA(scale for the assessment and rating of ataxia) and gait sub-scores exhibited a noteworthy improvement of 20-50%[57]. Although our ndings implicate that LM-021, LMDS-1, LMDS-2, and tafamidis targeting in ammasome and IL-1β and IL-6 signaling pathways have the potential for the treatment of SCA3, these ndings should be validated in animal models in the future studies.…”
mentioning
confidence: 65%
“…In an open-label pilot study, patients with SCA3 receiving IVIG treatment demonstrated improvement in the clinical disability scores. Following the nal course of IVIG treatment, total SARA(scale for the assessment and rating of ataxia) and gait sub-scores exhibited a noteworthy improvement of 20-50%[57]. Although our ndings implicate that LM-021, LMDS-1, LMDS-2, and tafamidis targeting in ammasome and IL-1β and IL-6 signaling pathways have the potential for the treatment of SCA3, these ndings should be validated in animal models in the future studies.…”
mentioning
confidence: 65%